Health Counseling on Early Initiation of Breastfeeding (IMD) and Exclusive Breastfeeding for Third Trimester Pregnant Women: Penyuluhan Kesehatan Tentang Inisiasi Menyusu Dini (IMD) dan ASI Eksklusif Pada Ibu Hamil Trimester III - Rahmawati; Waode Syahrani Hajri; La Rangki; Ida Mardhiah Arfini (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
Early Initiation of Breastfeeding is the provision of Mother's Milk (ASI) to the baby in the first hour after birth, where the baby is placed on the mother's chest and allows the baby to find the mother's nipple. Early Breastfeeding Initiation (IMD) is one way to reduce the Infant Mortality Rate (IMR). The purpose of this community service is to increase public knowledge (pregnant women) about Early Initiation of Breastfeeding and exclusive breastfeeding. The method used was counseling with lectures, discussions, and questions and answers as well as pre and post tests on Early Initiation of Breastfeeding and exclusive breastfeeding. The counseling participants were pregnant women who visited the KIA Poly Hospital of Aliyah Kendari Hospital as many as 20 people. The result was that the participants were very enthusiastic in watching and participating in the PkM activities. The pre-test of participants' knowledge was carried out by the service team and after the counseling, the mother's knowledge was also measured. The conclusion of this service is that there is an increase in knowledge of pregnant women about Early Initiation of Breastfeeding and exclusive breastfeeding.